Сверхтуризм и туризмофобия: новые явления или старые проблемы? : OVERTOURISM AND TOURISMOPHOBIA: NEW PHENOMENA OR OLD PROBLEMS? - Аигина Екатерина Вячеславовна (Современные проблемы сервиса и туризма, 2018)
Статья открывает новое в России дискуссионное направление исследований в области туризма. Она посвящена проблеме сверхтуризма, актуальной для растущего числа туристских дестинаций в мире. Раскрывается содержание понятия сверхтуризма. Предпринимается попытка теоретического осмысления нового явления. Большое внимание уделяется научному обоснованию пределов роста и устойчивости развития туризма. Рассматривается эволюция подходов к исследованию возможностей развития туризма и степени его воздействия на туристские объекты и местные сообщества через определение допустимой туристской нагрузки. Дается сравнение подходов к исследованию устойчивого туризма и принципов ответственного туризма как альтернативы сверхтуризму. Раскрыты факторы, стимулирующие сверхтуризм, и его социальные, экологические и экономические последствия. Систематизированы и выделены организационные, экономические, правовые, маркетинговые меры по регулированию туристских потоков в целях снижения остроты проблем сверхтуризма. Подробно освещены примеры проявления сверхтуризма на уровне страны (Исландия), популярной туристской дестинации (Венеция) и отдельного туристского объекта (парк Гуэля, Испания), рассмотрены предлагаемые пути решения возникающих в них проблем сверхтуризма, которые нацелены на создание более благоприятных условий для проживания местных жителей и для посещения этих мест туристами. Статья содержит большой объем актуальной статистической информации по проблемам сверхтуризма. : The paper starts a new discussion line in tourism research in Russia. It deals with the problem of overtourism which is relevant for the increasing number of tourist destinations around the world. The nature of overtourism notion is revealed. The author makes the attempt for theoretical understanding the new phenomena. Special attention is paid to scientific support of the limits to growth and sustainable tourism development. The article discusses evolution of initiatives in researching tourism development opportunities and tourism impact on attractions and local communities by means of carrying capacity assessment. The author compares sustainable tourism studies and the principles of responsible tourism as an alternative to overtourism. Factors that support overtourism and its social, ecological and economic consequences are revealed. The article systematizes and indicates organisational, monetary, legal and marketing measures for tourist flows regulation in order to reduce overtourism crucial problems... The paper starts a new discussion line in tourism research in Russia. It deals with the problem of overtourism which is relevant for the increasing number of tourist destinations around the world. The nature of overtourism notion is revealed. The author makes the attempt for theoretical understanding the new phenomena. Special attention is paid to scientific support of the limits to growth and sustainable tourism development. The article discusses evolution of initiatives in researching tourism development opportunities and tourism impact on attractions and local communities by means of carrying capacity assessment. The author compares sustainable tourism studies and the principles of responsible tourism as an alternative to overtourism. Factors that support overtourism and its social, ecological and economic consequences are revealed. The article systematizes and indicates organisational, monetary, legal and marketing measures for tourist flows regulation in order to reduce overtourism crucial problems. Examples of overtourism manifestation at national level (the case of Iceland), popular tourist destination (the case of Venice) and particular tourist site (the case of Park Güell, Spain) are discussed in details. The ways of responding overtourism problems intended to make extra favourable conditions for local residents and for tourists who visit these destinations are considered. The article contains a large amount of up-to-date statistical data on overtourism problems. function show_eabstract() { $('#eabstract1').hide(); $('#eabstract2').show(); $('#eabstract_expand').hide(); } ▼Показать полностью